The seventh book of the Stromateis : proceedings of the Colloquium on Clement of Alexandria (Olomouc, October 21-23, 2010) - Havrda, Matyáš, 1972-; Hušek, Vít.; Plátová, Jana. (Vigiliae Christianae, Supplements, 2012)
The seventh book of the Stromateis is the culmination of Clement of Alexandria's ethic. Introduced as an apology of the piety of the perfect Christian (the 'gnostic'), it broaches such topics as divine pedagogy, angelology, superstition, prayer, assimilation to God, martyrdom, eschatology, and the criteria of orthodoxy. This volume contains sixteen studies dealing with all major themes of the seventh book and the method of their presentation. It includes a Clementine bibliography of the last fifteen years and two appendices concerned with Clement's 'Hymn to Christ the Saviour.' The publication may serve as a companion to the reader of Stromateis VII and as a compendium of contemporary scholarship dealing with major aspects of Clement's thought in general.